The distribution of brown marmorated stink bug (Halyomorpha halys (Stål, 1855); Hemiptera: Pentatomidae) in the Northeast part of the Carpathian Lowland (West Ukraine) - Szanyi, Szabolcs; Ősz, Aletta; Szanyi, Kálmán; Potish, Ludvig; Nagy, Antal (Acta Agraria Debreceniensis, 2022)
Halyomorpha halys (Stål, 1855) spread rapidly during the last five years and became common and abundant in Central Europe, especially in the urban environment. In the Carpathian basin, the West Ukrainian Transcarpathia county was the last region where this species has not been found yet. The first specimens of this invasive pest were sampled in Velyka Dobron’ in 2018 and in 2019 it was found in another neighbouring village and cities of Chop, Berehove and Uzhhorod. The data provided here is the first for West Ukraine and the second for the country following the published record from Odessa (SE Ukraine). Although H. halys is still less abundant and occupied mainly urban habitats, it will certainly cause nuisance for peoples and damages for farmers in the near future.